2013
DOI: 10.1002/ijc.28242
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for false positive and for false negative test results in screening with fecal occult blood testing

Abstract: Differences in the risk of a false negative or a false positive fecal immunochemical test (FIT) across subgroups may affect optimal screening strategies. We evaluate whether subgroups are at increased risk of a false positive or a false negative FIT result, whether such variability in risk is related to differences in FIT sensitivity and specificity or to differences in prior CRC risk. Randomly selected, asymptomatic individuals were invited to undergo colonoscopy. Participants were asked to undergo one sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 35 publications
3
43
6
1
Order By: Relevance
“…If this is the case, the question remains open as to how long this should be done beforehand. In 2 clinical trials, the specificity of the iFOBT was lower in regular NSAID users [7, 8]. This conclusion is in stark contrast to a multivariate analysis conducted on 193 veterans that found no association between regular use of NSAID and a false-positive iFOBT (OR 0.85) [9].…”
Section: Discussioncontrasting
confidence: 42%
“…If this is the case, the question remains open as to how long this should be done beforehand. In 2 clinical trials, the specificity of the iFOBT was lower in regular NSAID users [7, 8]. This conclusion is in stark contrast to a multivariate analysis conducted on 193 veterans that found no association between regular use of NSAID and a false-positive iFOBT (OR 0.85) [9].…”
Section: Discussioncontrasting
confidence: 42%
“…Both studies reported a higher test sensitivity in men. 18,19 Furthermore, the higher FPR in men may be the result of a lower test specificity. Specificity is defined by the proportion of people without the disease who also test negative.…”
Section: Discussionmentioning
confidence: 97%
“…This is in line with the results of the 2 aforementioned colonoscopy screening studies. 18,19 In addition, we calculated the FPR for the subjects with a positive FIT who had no adenoma or CRC at follow-up colonoscopy (ie, only hyperplastic polyps or no findings at all). After also including the nonadvanced adenomas, we did not see any differences between men and women for the different cut-off levels (Appendix 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations